The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/capr.12403
|View full text |Cite
|
Sign up to set email alerts
|

Therapists' perspectives on working with clients taking psychiatric drugs: Findings from a mixed‐methods survey

Abstract: Objectives: Around 26% of the British adult population are prescribed psychiatric drugs each year. Most therapists (counsellors, psychotherapists and psychologists) provide therapy to some clients taking prescribed psychiatric drugs. This study aimed to better understand the experience, knowledge, training and concerns of therapists working therapeutically with clients prescribed psychiatric drugs. Design:This was a survey study, generating both quantitative and qualitative data. Methods:The online survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One Canadian study, for example, has reported that 74.2% of respondents indicated they did not have adequate support to prevent and address the misuse of prescription drugs (Porath‐Waller et al, 2015). While counsellors have also acknowledged the need for evidence‐based information about substance use and support for client‐based empowerment (Blair et al, 2021), many do not feel adequately trained to work with clients who have substance use disorders (Martin et al, 2016). Counsellors are well placed to provide evidence‐based interventions to assist clients during withdrawal from overused psychoactive substances and are frequently asked about the impact of psychiatric drugs on therapy (Blair et al, 2021; Dorais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One Canadian study, for example, has reported that 74.2% of respondents indicated they did not have adequate support to prevent and address the misuse of prescription drugs (Porath‐Waller et al, 2015). While counsellors have also acknowledged the need for evidence‐based information about substance use and support for client‐based empowerment (Blair et al, 2021), many do not feel adequately trained to work with clients who have substance use disorders (Martin et al, 2016). Counsellors are well placed to provide evidence‐based interventions to assist clients during withdrawal from overused psychoactive substances and are frequently asked about the impact of psychiatric drugs on therapy (Blair et al, 2021; Dorais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While counsellors have also acknowledged the need for evidence‐based information about substance use and support for client‐based empowerment (Blair et al, 2021), many do not feel adequately trained to work with clients who have substance use disorders (Martin et al, 2016). Counsellors are well placed to provide evidence‐based interventions to assist clients during withdrawal from overused psychoactive substances and are frequently asked about the impact of psychiatric drugs on therapy (Blair et al, 2021; Dorais et al, 2020). Evidence‐based psychological support for BZD withdrawal includes cognitive behavioural therapy, motivational interviewing and supportive counselling (Darker et al, 2015; Dutra et al, 2008; Parr et al, 2009; Reeve et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation